ARTISTIC PARAMETERS OF THE COMMON TURKIC MONUMENTS OF LITERATURE OF THE 11-13th CENTURIES IN KARACHAY-BALKAR ORAL POETRY - T. Sh. BITTIROVA; L. H. MAHIEVA (Кавказология, 2019)
Based on the comparative analysis method, the article establishes the proximity of small genres of Karachai-Balkar folklore, phraseological units, ethnographic realities to the content of such well-known common Turkic monuments of the Middle Ages, like Yusuf Balasagunsky's «Kutadgu bilik», Makhmud Kashgar's «Divan lugat it-Türk» and «Codex Cumanicus». The authors explain the correspondence of many literary and linguistic facts with the ethnogenetic affinity and the rather isolated living of the Karachay-Balkarian people, who have preserved the substrate-wide parameters of their language. The proximity of linguistic art means, stylistic techniques of the monument, compiled by M. Kashgarsky, and the facts of modern Karachai-Balkar literature (especially poetry of the pre-Soviet period) gives grounds to consider the «Dictionary» as an anthology of linguistic and artistic sources of Karachai-Balkar literature and culture, as well as of literatures and cultures of other Turkic peoples.